Prevalence of anaemia, iron deficiency, iron deficiency anaemia and risk factors for iron deficiency in kelantanese children - Ali Shibramulisi, Siti Noor (2001)
Iron deficiency (ID) is the most common nutritional deficiency in childhood (Dallman et ai, 1980). Iron deficiency anaemia (IDA) in children less than 2 years causes behavioural abnormalities and developmental delay (Lozoff et ai, 1991). Prevalence figures are therefore needed to estimate the scope of the problem and identification of potential risk factors associated with 10 and IDA will help to formulate preventive strategies.